2007
DOI: 10.1007/s12020-007-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol Pygeum africanum regulates prostate cancer in vitro and in vivo

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 43 publications
(61 reference statements)
0
59
0
1
Order By: Relevance
“…Male TRAMP mice (10) on a C57BL6/J background were raised in-house as described previously (11). The mice were fed the specific diets from 5 wk until 5 mo of age (18-22 mice per treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…Male TRAMP mice (10) on a C57BL6/J background were raised in-house as described previously (11). The mice were fed the specific diets from 5 wk until 5 mo of age (18-22 mice per treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…TRAMP mice, a mouse model to investigate PCa, exhibited a reduction of PCa incidence compared to the control group after feeding with Pygeum africanum extract (Shenouda et al, 2007).…”
Section: Roell and Baniahmadmentioning
confidence: 98%
“…Herby, the pulverized bark is incorporated into capsules and commercially available as the remedy Tadenan ® and in other European countries under various different trade names (Ishani et al, 2000). In the USA phytotherapeutic agents like extracts of Pygeum africanum have been marketed for prostate health including PCa prevention and treatment (Shenouda et al, 2007).…”
Section: Roell and Baniahmadmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAMP mice fed with P. africanum showed a significant reduction (P = 0.034) in prostate cancer incidence (35%) compared to casein fed mice (62.5%). P. africanum therefore has a significant role in regulation of prostate cancer both in vitro and in vivo and therefore may be a useful supplement for people at high risk for developing prostate cancer (Shenouda et al, 2007). Katz (2002) had observed that the consumption of isoflavones found in legumes and other plants is related to lower rates of BPH and prostate cancer among Asian men (Katz, 2002).…”
Section: Figure 6: Stages In Cancer Prevention Researchmentioning
confidence: 99%